AFFORDANCES DA COIL PARA PROMOVER INTERNACIONALIZAÇÃO EM CASA E FORMAÇÃO DE PROFESSORES DE INGLÊS: ANÁLISE DE UMA EXPERIÊNCIA ENTRE UFES E UNIVERSIDADE DE COVENTRY - Có, Elisa Prado (2021)
The aim of this research study was to analyze the affordances perceived by students of the discipline Supervised Internship of the Federal University of Espírito Santo (UFES), pre-service teachers, about the use of the Collaborative Online International Learning (COIL) as a strategy of Internationalization at Home – IaH – and teacher formation. A COIL intervention was launched during this discipline in partnership with the students of a similar discipline from Coventry University, in England. The data were produced based on the design and implementation and analysis of a COIL project, including the following instruments: participant observation, the portfolios developed by students during the discipline, a questionnaire about the students’ perceptions on the COIL project and a focus group. The theoretical background includes the concept of affordances (VAN LIER, 2004), linked to the concepts of Epistemologies of the South and in post-colonial and decolonial theories (for example SANTOS, 2007, 2009, ASHCROFT; GRIFFITHS; TIFFIN, 1989, QUIJANO, 2005). This research study can be characterized as a case study (YIN, 2001) with a qualitative analysis. The results of the analysis suggest that the COIL intervention enabled a critical and decolonial reflection to the students as well as a new and unique international experience, completely virtual. This experience revealed new perspectives for the teaching and learning of English and for the uses of digital technologies. It is a possibility to promote internationalization at home and teacher formation to a global context.